Patients’ Preference in Selecting a Dental Practitioner based on Gender - Ayesha Aijaz Bhatti; Fatima Wasif; Zarnab Yousaf; Zunaira Iqbal; Asma Rafi Chaudhry; Sehrish Zaffar (Journal of University College of Medicine and Dentistry)
Objective: To examine the prevalence of gender-based selection of dental practitioners among male and female patients in the Out Patient Department (OPD) of the Institute of Dentistry, CMH Lahore Medical College, and to identify factors influencing their choice.